Petrarch in English: - Hodder, M (2013)
This thesis is concerned with one key aspect of the reception of the vernacular poetry of Francesco Petrarca (Petrarch), namely translations and imitations of the Rerum vulgarium fragmenta (Rvf) and Triumphi in English. It aims to provide a more comprehensive survey of the vernacular Petrarch’s legacy to English literature than is currently available, with a particular focus on some hitherto critically neglected texts and authors. It also seeks to ascertain to what degree the socio-historical phenomena of religion, politics, and culture have influenced the translations and imitations in question. The approach has been both chronological and comparative. This strategy will demonstrate with greater clarity the monumental effect of the Elizabethan Reformation on the English reception of Petrarch. It proposes a solution to the problem of the long gap between Geoffrey Chaucer’s re-writing of Rvf 132 and the imitations of Wyatt and Surrey framed in the context of Chaucer’s sophisticated imitative strategy (Chapter I). A fresh reading of Sir Philip Sidney’s Astrophil and Stella is offered which highlights the author’s misgivings about the dangers of textual misinterpretation, a concern he shared with Petrarch (Chapter II). The analysis of Edmund Spenser’s Amoretti and Epithalamion in the same chapter reveals a hitherto undetected Ovidian subtext to Petrarch’s Rvf 190. Chapter III deals with two English versions of the Triumphi: I propose a date for Lord Morley’s translation which suggests it may be the first post- Chaucerian English engagement with Petrarch; new evidence is brought to light which identifies the edition of Petrarch used by William Fowler as the source text for his Triumphs of Petrarcke. The fourth chapter constitutes the most extensive investigation to date of J. M. Synge’s engagement with the Rvf, and deals with the question of translation as subversion. On the theoretical front, it demonstrates how Synge’s use of “folk-speech” challenges Venuti’s binary foreignising/domesticating system of translation categorisation.